Evaluation of agroecological processes implemented in olive production systems: an analysis in Boyacá, Colombia - Barrera-Siabato, Andrea Isabel; Castro-Triana, Ana María; Colmenares-Cruz, Ramiro Andrés; Moreno-Lopez, Nidia Milena (Frontiers in Sustainable Food Systems, 2025)
The development of agriculture based on an agroecological approach has become a strategic commitment for various national and international organizations. This commitment seeks to establish new production alternatives capable of meeting food market demands while addressing the impacts of climate variability and climate change. Within this framework, olive cultivation has gained traction in Colombia, particularly in regions where other crops fail to adapt, sparking interest among farmers and rural development researchers. Nonetheless, this production model faces significant limitations, especially in the comprehensive development of the value chain, as Colombia’s olive sector struggles to consolidate the production of table olives and olive oil. Combined with the rising costs of soil amendments and synthetic fertilizers, this situation limits the strengthening of productive chains and, consequently, the socioeconomic advancement of farmers. This document therefore aims to analyze available information and identify successful experiences involving the adoption of agroecological practices in olive farming, with a focus on enhancing producers’ social and economic outcomes by addressing different components of the value chain. To achieve this, the PRISMA methodology was applied to define search thresholds and establish inclusion and exclusion criteria, guiding the research toward its objective. The results show that olive farming is among the most developed agricultural value chains in several European and Asian countries; however, some regions in Latin America have also gained relevance in olive and olive oil. Production and marketing. In addition, certain countries have introduced incentives to encourage sustainable agricultural systems, both to mitigate the environmental impacts of farming and to strengthen markets for healthy food products. In Colombia, current research on olive cultivation highlights its potential in the country’s central region, but also points to a lack of studies supporting the development of the value chain as a climate adaptation strategy. In areas where other crops are not viable, olive farming could offer a sustainable land use alternative and contribute to territorial development through the reinforcement of resilient agri-food systems.